Effects of different arm-specific training on the pull-up performance of climbers - Devise, M.; Vigouroux, L. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Sport climbing performance is known to be highly related to strength and endurance in upper limb. Trainers and climbers therefore focus on developing the ability of the fingers to hang on holds and the arms to pull up from one position to another. Although finger-specific assessment and training methods are widely analysed in the literature, no study has yet quantified the effects of arm-specific training. These programs usually consist of different muscle contraction regimes (isometric, eccentric…). The aim of this study is then to compare the effects of these different types of training on climbers pull-up capabilities.